2012
DOI: 10.2337/dc11-1942
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Taspoglutide Monotherapy in Drug-Naive Type 2 Diabetic Patients After 24 Weeks of Treatment

Abstract: OBJECTIVETo evaluate the efficacy and safety of taspoglutide monotherapy in drug-naive patients with type 2 diabetes inadequately controlled.RESEARCH DESIGN AND METHODSIn this 24-week double-blind, placebo-controlled, multicenter trial, 373 patients with type 2 diabetes naive to antihyperglycemic medication were randomized to weekly subcutaneous taspoglutide 10 or 20 mg or placebo.RESULTSHbA1c reductions from baseline were greater with taspoglutide 10 and 20 mg than placebo (least squares mean [SE] changes: –1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 2 publications
(2 reference statements)
3
24
1
Order By: Relevance
“…Although pioglitazone therapy has been associated with weight gain (20, 21), patients enrolled in this trial had been on pioglitazone therapy for 12 wk or more before trial initiation. The weight loss observed with taspoglutide is consistent with previous reports (13)(14)(15). Raz et al (15) reported a similar progressive weight loss with taspoglutide 20 mg QW over 24 wk, resulting in a significantly greater weight loss compared with placebo (Ϫ2.25 Ϯ 0.30 kg, P ϭ 0.02).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although pioglitazone therapy has been associated with weight gain (20, 21), patients enrolled in this trial had been on pioglitazone therapy for 12 wk or more before trial initiation. The weight loss observed with taspoglutide is consistent with previous reports (13)(14)(15). Raz et al (15) reported a similar progressive weight loss with taspoglutide 20 mg QW over 24 wk, resulting in a significantly greater weight loss compared with placebo (Ϫ2.25 Ϯ 0.30 kg, P ϭ 0.02).…”
Section: Discussionsupporting
confidence: 81%
“…In phase II and III trials, patients with T2DM treated with once-weekly (QW) sustained-release formulation of taspoglutide demonstrated good glycemic control with minimal hypoglycemic risk and weight loss (13)(14)(15). The purpose of this study (T-emerge 3) was to assess the efficacy and safety of QW taspoglutide in patients with T2DM inadequately controlled with metformin plus pioglitazone compared with placebo after 24 wk of treatment.…”
mentioning
confidence: 99%
“…11,[29][30][31] Two double-blind placebo-controlled studies showed the highest dose of TAS (20 mg once weekly) was associated with higher incidences of nausea (52% and 31%) and vomiting (22% and 17.8%) than placebo. 32,33 Dose-response studies showed a dosedependent increase of nausea from EX5BID (range, 3-39%) to EX10 BID (range, 13-51%) and an increase of GI AEs from LIR0.6QD to LIR1.2QD to LIR1.8QD. [34][35][36][37][38][39][40] According to the results obtained, we found that patients treated with high doses of EX had a higher risk of developing nausea than those treated with low doses of it.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this special biochemical engineering is to protect GLP-1 from deactivation by the DPP IV enzyme. This increases solubility, reduces renal clearance, and increases the pharmacodynamics duration [43][44][45].…”
Section: Igg4-rd and Diabetesmentioning
confidence: 99%
“…The peptide portion of dulaglutide was designed to be as high as 90% homologous to endogenous human GLP-1. Nonetheless, immunoadhesion of the Fc protein to an end organ molecule (receptors, an enzyme, or ligand) helps inhibit autoimmune and inflammatory processes against it [43,52,53]. In the AWARD 1 trial-a multicenter trial comparing dulaglutide to exenatide-added pioglitazone and metformin (n=987); dulaglutide led to antibodies in 1.8% while the exenatide-treated group developed antibodies in 48% of the patients [53].…”
Section: Immunogenicitymentioning
confidence: 99%